The Effect of Population Size, Minimum Wage, and Gross Regional Domestic Product (GRDP) on Unemployment in East Java Province - Mochammad Heru Widodo; Muhamad Muliono; mohamadfathurrohman (Jurnal Ragam Pengabdian, 2026)
This study aims to examine the effect of population size, minimum wage, and Gross Regional Domestic Product (GRDP) on the open unemployment rate in East Java Province. This research is an explanatory study that explains the relationships among variables. It seeks to analyze the influence of independent variables on the dependent variable through hypothesis testing using statistical analysis. The study employs time series data over a ten-year period from 2015 to 2024. Using a quantitative approach, multiple linear regression analysis is applied to determine the effect of the independent variables on the dependent variable. The results indicate that, partially, population size has a positive and significant effect on the open unemployment rate, the minimum wage has no significant effect on the open unemployment rate, and Gross Regional Domestic Product has a negative and significant effect on the open unemployment rate. Simultaneously, population size, minimum wage, and Gross Regional Domestic Product jointly affect the open unemployment rate in East Java Province during the period 2015–2024.